PENGARUH WAKTU PENYIANGAN TERHADAP PERTUMBUHAN DAN HASIL PADI (Oryza sativa L.) YANG DIBUDIDAYAKAN SECARA SRI (The System of Rice Intensification) (The Effect Of Weeding Time Toward The Growth of Paddy at System Of Rice Intensification) - . Buhaira (Bioplantae, 2013)
This research aim is to find out the time of weeding for better growth and yield of rice cultivated which is used SRI method. Research was conducted on wet land located on Koto Panjang Ikur Koto (KPIK) village, Koto Tangah District, Padang City. Experiment was arranged in a randomized block design with nine times replication. Time of weeding comprised three levels, namely: a week before planting and a week after planting, one and three weeks after planting, and two and four weeks after planting. Variables observed were growth (number of tillers, leaf area index (LAI), averaged net assimilation rate (NAR), averaged crop growth rate (CGR), yield components (number of productive tillers, percentage of empty grain per tiller, filled grain weight per tiller, and 1000 seeds weight) and GKG (drygrain milled) yield per hectare. Data were analyzed using analysis of variance. Significant variables were then analyzed using Honest Significant Difference (HSD). Results showed that time of weeding had significant effect on growth and yield of rice cultivated using SRI method. Best growth and highest yield were obtained by weeding application in two and four weeks after planting.Key words: SRI, weed, weeding.